Forest Canopy Density Effects on Snowpack Across the Climate Gradients of the Western United States Mountain Ranges. Issue 1 (12th January 2022) - Sun, Ning; Yan, Hongxiang; Wigmosta, Mark S.; Lundquist, Jessica; Dickerson‐Lange, Susan; Zhou, Tian
Abstract: Controlled field experiments to disentangle the effect of canopy density from the effect of climate on snowpack dynamics are limited by the underlying linkage between canopy density and climate. Thus, based on observations alone, it is not well understood how variations in canopy density can affect snow processes under different climate regimes. To address this knowledge gap, this study uses a physics‐based modeling approach to evaluate the sensitivity of snowpack dynamics to variations in canopy density across the climate gradients of the Western U.S. as represented by 228 Snow Telemetry (SNOTEL) sites. Within the model, we uniformly parameterize the canopy across sites to represent an idealized forest with high, medium, and low canopy density, respectively. The results illustrate that the effect of canopy density on the peak snow water equivalent (SWE) and duration of under‐canopy snowpack is sensitive to winter climate (i.e., climatological winter precipitation and temperature). As canopy density decreases, the greatest increase in peak SWE and snowpack duration is found in wet/warm and dry/cold climates, where snowpack under low‐density forest lasts longer than that in the open. In comparison, peak SWE and snowpack duration in wet/cold climates are less sensitive to changing canopy density. Thus, forest management actions (e.g., thinning and clearing) are likely to have disparate impacts on snow depending on local winter climate. Climate sensitivity of under‐canopy snowpack suggests that snowpack duration under dense canopy in presently warm winter climates is expected to experience the greatest reduction under a warming climate. Plain Language Summary: In the Western U.S., forest management (e.g., clearing and thinning) has great potential for altering snow processes, which is particularly important for locations susceptible to low flows in the summer. With limited observations available to evaluate climate‐forest‐snow relationships, there is a lack of knowledge about how changing forest density can affect snow water storage and snowpack duration under different climate conditions. To address this gap, this study uses a physics‐based snow model to simulate snow processes under changing canopy density for over 200 locations representative of the Western U.S. climate diversity. Results suggest that the effect of canopy density on snowpack water storage and duration varies with winter climate, and thus the effect of forest management on snow and water resources can vary substantially with climate. In wet/warm and dry/cold climates, a decrease in canopy density generally increases snowpack duration such that a low‐density forest keeps snowpack longer than an open area in the same location. From the forest management perspective, canopy thinning in these climates provides better chances than forest clearing for enhancing snowpack duration and storage. In wet/cold climates, snowpack duration is less sensitive to changing canopy density. Key Points: Canopy density effect on peak snow accumulation and snowpack duration varies with winter climates Canopy thinning is most effective in wet/warm winter climates for improving snowpack duration Greatest decrease in snowpack duration under warming is anticipated for snowpack under dense canopy in presently warm winter climates